2013
DOI: 10.1002/ejoc.201300607
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Sonogashira Reactions of 1,4‐Dibromo‐2‐(trifluoromethyl)benzene: Synthesis and Properties of Fluorinated Alkynylbenzenes

Abstract: Site‐selective Sonogashira cross‐coupling reactions of 1,4‐dibromo‐2‐(trifluoromethyl)benzene have been performed, affording a variety of functionalized alkynyl‐substituted (trifluoromethyl)benzenes. The site selectivity, in favor of position C‐4, was confirmed by 13C NMR and 1H–13C HMBC NMR measurements, X‐ray crystal structure analysis as well as DFT calculations. Furthermore, the mesomorphic properties and optical textures were examined by differential scanning calorimetry and polarized optical microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…To be further convinced of the importance of the present reaction, we carried out an additional transformation of the coupling adduct 4n to a CF 2 CF 2 -containing π-conjugates molecule, a fluorinated tolane derivative, applicable to promising functional materials, such as light-emitting and liquid-crystalline materials ( Scheme 3 ) [ 39 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…To be further convinced of the importance of the present reaction, we carried out an additional transformation of the coupling adduct 4n to a CF 2 CF 2 -containing π-conjugates molecule, a fluorinated tolane derivative, applicable to promising functional materials, such as light-emitting and liquid-crystalline materials ( Scheme 3 ) [ 39 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li and Hu reported organic compounds consisting of ethynyl bridges (80)(81)(82) which were employed in construction of OFET devices (Figure 5). [106] CV studies revealed the irreversible redox behavior of compounds 80 and 81 and quasi- reversiblity behavior of 82.…”
Section: Application Of Polyalkynylated Pahs In Ofet Devicesmentioning
confidence: 99%
“…Among the trifluoromethyl substituted alkynylated compounds 51 , 52 and 54 (Figure 1), both 51 and 52 displayed four transitions in their absorption spectra [81] . Due to the mesomeric and electron inductive effect, the compounds containing electron‐donating groups ( 51 b – g , 52 b – g ) demonstrated redshift in absorption as well as in emission spectra.…”
Section: Photophysical Properties Of Pahsmentioning
confidence: 99%
See 2 more Smart Citations